The brain's polymath: Emerging roles of microglia throughout brain development. (April 2023) - Wong, Fong Kuan; Favuzzi, Emilia
Abstract: Microglia, the resident brain immune cells, have garnered a reputation as major effectors of circuit wiring due to their ability to prune synapses. Other roles of microglia in regulating neuronal circuit development have so far received comparatively less attention. Here, we review the latest studies that have contributed to our increased understanding of how microglia regulate brain wiring beyond their role in synapse pruning. We summarize recent findings showing that microglia regulate neuronal numbers and influence neuronal connectivity through a bidirectional communication between microglia and neurons, processes regulated by neuronal activity and the remodeling of the extracellular matrix. Finally, we speculate on the potential contribution of microglia to the development of functional networks and propose an integrative view of microglia as active elements of neural circuits.